The Effect of Interactive Media Based on Animated Video on Natural Science Process Skills in Elementary School - Sinambela, Bella Silfitri; Pratiwi, Indah (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to describe interactive media for enhancing student learning outcomes and to analyze the impact of animated video-based interactive media on science process skills. The study utilized a quantitative Nonequivalent Control Group Design with a pretest-posttest involving two classes, IV-A and IV-B, each consisting of 26 students. The instrument used in this study was a multiple-choice test obtained from a test bank. Quantitative data analysis employed statistical procedures, including descriptive and inferential statistics. Based on the research findings, the significance value obtained from the Independent Sample T-Test was 0.00, which is less than 0.05. This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, concluding that animated video-based interactive media significantly influences science process skills. The analysis also revealed that animated video-based interactive media has an 80% impact on science process skills, demonstrating that this type of media effectively enhances science process skills in fourth-grade elementary school students.